Taste It Enterprise / Clara Justin ... [et al.] - Justin, Clara; Othman, Siti Khadizah; Soupin, Caroline; Mohd Zain, Fatimah; Haji Mumin, Salleh (2015)
This business is based on partnership where it consists of five (5) members which hold important positions in the company such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 250,000 where the total contribution of each member is RM50,000 To say about fast food, many of us think that eating fast food is not good for health, but bribed by the public, social media and other related matters is the content of fast food. But not in Taste It, because we are concerned about the quality in the production of product release our core offerings of burgers, from a variety of ways ranging from the selection of raw materials, the production of minced meat, mix bread dough, fresh vegetables, drinks and fries always be an option for those who wish to enjoy any kind in their spare time. In finding variations to Taste It, we took our meals in the main concept of the meal also for health, which for the production of bread dough, we provide some type of bread that can be eaten by all walks of life, especially for those who want to adopt a healthy lifestyle. Bread that mentioned among bamboo charcoal buns, hi-fiber buns, gluten-free buns, cereal buns, rice made buns and eggless buns. All this bread representing diet for those who want to enjoy a burger but in a healthy condition. Also for the content of burgers, the meat used is 100% meat such as beef, chicken, duck and also seafood such as prawn, crab, fish fillet and few more. The sound maybe impossible to do, but through the help of several agencies involved, all this process has been monitored and fine-tuned to ensure the quality output our burgers. In addition, the selection of business site also become a focal point, for our shop is located near the ferry terminal, which has become one of the main city attractions in Kota Kinabalu not only by foreign tourists but also from local tourist ever since its privatization in February 2006. It also serves as the only ferry terminal for Labuan-bound passengers as well as the main and cheapest boat terminal for the Tunku Abdul Rahman Marine Park and Gayana Island. Our business is expected to commence on 2016 and our vision is to make our company well-known, established and satisfied by our customer in order to expand our business and to attract other fast food company to deal with us with a better price. This will be realized by the full cooperation and efforts among the partners to promote our company. Based on the objectives above, we are venturing into food industry. Burger production has the potential of being a profitable business if it is done in modem way with large scale and systematically managed. We will expect that our business will become more develope in the near future because with the new innovation in our burger, the demand will increase not only during any occasion but it might be a new daily snack. This will give more advantages for us to make our product more profitable and stable in the long run.